Global banking, financial markets and crises - Jeon, Bang Nam, 1954-; Olivero, María Pía (International finance review ;, 2013)
One of the most salient features of the 2007-9 global financial crisis was the role played by global banking and multinational banks in transmitting international financial shocks and maintaining credit stability in domestic and international financial markets. This edited volume on "Global Banking, Financial Markets and Crises" contains original papers that examine various issues concerning the changing role of global banks during crisis periods. The papers in this volume also address the impact of global financial crises on multinational banking, domestic and international financial markets, and emerging economies. Particular emphasis is given on the regional experiences of cross-border banking, domestic and global financial market integration, portfolio investment, cross asset market spillovers, cross country crisis contagion, monetary policy transmission mechanism, and the role of foreign banks during crisis periods compared to non-crisis periods in various advanced countries as well as emerging economies. This volume also presents various important policy implications and lessons from recent global financial crises.